Liability Driven Investment Analysis for Hajj Financial Management Optimization using Analytic Network Process Approach - Juniastanti, Erwinda Anggraini; Ratnawati, Nirdukita; Jayaprawira, Acep Riana; Achsani, Muhammad Nur Faaiz Fathah; Arief, Zaenal (Global Review of Islamic Economics and Business, 2023)
In this research, a liability-driven investment strategy is determined which aims to optimize hajj financial management using the Analytic Network Process approach. Based on the results of Benefit, Opportunity, Cost and Risk (BOCR) approach, it shows that in a liability-driven investment strategy, the benefit (excess) and risk components are the most important factors that investors pay attention to. In determining alternative liability-based investment strategies, there are 2 (two) approaches, either by carrying out portfolio immunization (duration matching) or cash flow matching (cash-flow matching). From these two strategies, it was found that the portfolio immunization strategy was the most suitable strategy to be implemented at BPKH in terms of the return and risk dimensions. Then the strategy is implemented through a portfolio-mix combinations between hedging portfolios and growth portfolios (return generating portfolios), and the most appropriate composition based on the dimensions of returns and risks is the hedging portfolio whose magnitude is above the growth portfolio. It can be said that BPKH can carry out a liability-driven investment strategy through a portfolio immunization strategy that contains a hedging portfolio (such as SBSN and corporate sukuk) that is larger than the growth portfolio (such as KIK EBAS, EBAS-SP, KIK DINFRA, KIK DIRE, Limited Investment Mutual Funds, and Direct Investment and Others). Originality/Value: The novelty of this study is analysing the hajj fund by BPKH in a deeper and specific extent by displaying future liability data.